Do Symptoms of Pelvic Floor Disorders Bias Maternal Recall of Obstetrical Events Up to 10 Years After Delivery?. Issue 3 (May 2015) - Chen, Crystal; Smith, LaPortia J.; Pierce, Christopher B.; Blomquist, Joan L.; Handa, Victoria L.
<x xml:space="preserve">Abstract</x> Objectives The aim of this prospective study was to investigate whether symptoms of incontinence and prolapse bias maternal recall of obstetrical events up to 10 years after delivery. Methods In this secondary analysis of data gathered from the Mothers' Outcomes After Delivery study, we compared obstetrical medical records with maternal recall of delivery events. We calculated the agreement between maternal recall and the medical record across 1821 deliveries from 1011 participants for events including macrosomia, mode of delivery, prolonged second of labor, episiotomy, spontaneous laceration, anal sphincter laceration, and operative delivery. Women with symptomatic pelvic floor disorders were identified through administration of the Epidemiology of Prolapse and Incontinence Questionnaire or a clinical history of therapy for a pelvic floor disorder. We determined whether agreement between maternal recall and the medical record differed for those with or without symptoms using the medical record as a criterion standard. Results Agreement between maternal recall and the medical record was excellent for macrosomia and forceps deliveries (κ > 0.8), fair to good for episiotomy (κ = 0.61) and anal sphincter laceration (κ = 0.57), and poor for spontaneous perineal laceration (κ = 0.41). Symptomatic pelvic floor disorders did not impact maternal recall of macrosomia, prolonged second stage, episiotomy, spontaneous laceration, or operative delivery. However, recall of anal sphincter lacerations was biased by symptoms of pelvic floor disorders. Specifically, symptomatic women were significantly more likely to report a history of anal sphincter laceration, regardless of whether a sphincter laceration was documented (P = 0.025). Conclusions Maternal recall of anal sphincter laceration may be biased by symptomatic pelvic floor disorders. In research based on maternal recall of obstetrical events, this could strengthen the apparent association between sphincter laceration and pelvic floor disorders.